Literacy of zakah: case of Malaysia - Allah Pitchay, Anwar; Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad (Lembaga Zakat Negeri Kedah, 2019)
Islam is a unique religion which emphasizes on the importance of charity. There are two (2) types of charity; (1) compulsory charity such as Zakah and (2) voluntary charity such as donation and Waqf. The past Islamic civilization has proven these charity tools have contributed to the development of a nation without debt-based financial instruments. Currently, we find these tools are no longer effective compared to the modern financial instrument which highly subscribed to debt-based. Therefore, the aims of the study are to explore the literacy of Muslim on Zakah basic knowledge. 200 questionnaires have been distributed using random sampling technique in 14 states and 2 federal territories of Malaysia (Persekutuan and Putrajaya). The questions are comprised of basic knowledge of Zakah. The findings show that majority of the respondents have common knowledge of Zakah but only one (1) technical question such as percentage of Zakah seems to be confused by the respondents. Many respondents answer not sure about the percentage of 2.5. Generally, the output indicates that Malaysian do aware on the role of Zakah from the Islamic perspective, thus, it is the responsibility of the operator of Zakah and Muslim to continuously educate the public especially the young generation on the importance of Zakat for the development of Muslim society and nation.